A series of 1,3-imidazoles and triazole-3-thiones based thiophene-2-carboxamides as anticancer agents: Synthesis and anticancer activity - Haggam, Reda Ahmed; Assy, Mohamed Gomma; Sherif, Mohamed Hassan; Galahom, Mohamed Mohamed (European Journal of Chemistry, 2018)
By addition of semicarbazide or phenylhydrazine hydrochloride to thienoylisothiocyanate (1) resulted in building of thiosemicarbazide derivative (2), triazole derivative (4) and thiophene-2-carboxamide (5), respectively. Basic cyclization of compound 2 led to formation of oxadiazine (3). Synthesis of thiadiazine derivative (6) was achieved via reaction of compound 5 and maleic anhydride in triethyl amine. Heating of compound 5 with ethyl chloroacetate or sodium ethoxide produced thiadiazine derivative (7) and triazolethione (8), respectively. Thiosemicarbazide derivative 11 was synthesized by addition of nicotinic hydrazide to compound 1. Refluxing of compound 11 with lead acetate afforded triazole (13). Moreover, acid and base mediated cyclizations of compound 11 gave thiadiazole (12) and 1,2,4-triazolethione (14) throughout thiophene intermediate, respectively. Addition of ethyl 2-aminothiophene-3-carboxylate to compound 1 formed thiourea (15) which was refluxed with ethoxide giving thiophene-3-carboxylic acid (16). Lastly, nucleophilic addition of amino phenol or ethylene diamine to compound 1 yielded oxazine structure (18) and imidazole derivative (19), respectively. The yields of the synthesized compounds were 61-95%. The detailed synthesis and spectroscopic data of the new compounds are reported.